1994
DOI: 10.1021/bi00200a014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Recombinant Monomer Hemoglobins (Component IV) from the Marine Annelid Glycera dibranchiata: Evidence for Primary Sequence Positional Regulation of Heme Rotational Disorder

Abstract: A description of the efficient high-level expression of the monomer hemoglobin (GMG4) from Glycera dibranchiata is presented. The cDNA described by Simons and Satterlee [Simons, P.C., & Satterlee, J.D. (1989) Biochemistry 28, 8525-8530] was subcloned into an expression system, and conditions were found that led to the production of large amounts of soluble apoprotein (rec-gmg). These conditions included lowering the temperature during the induction period and growth in a rich medium with a higher ionic strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…A clear picture of the extent of globin heterogeneity in this organism has emerged only recently, as a result of primary sequencing5, 6 and mass spectrometry 5–7. Those results have confirmed the individual uniqueness and homogeneity of the three major monomer hemoglobins, called components II, III, and IV (or alternatively GMH2, 3, and 4) that have been reproducibly isolated and characterized in this laboratory 3–8, 11–14, 24–39. Recently, the solution structure of the CO‐ligated Fe 2+ (reduced, ferrous) form of recombinant GMH4 (GMH4CO) was determined,38, 39 making it the first structure to be determined of one of our highly characterized monomer hemoglobins.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…A clear picture of the extent of globin heterogeneity in this organism has emerged only recently, as a result of primary sequencing5, 6 and mass spectrometry 5–7. Those results have confirmed the individual uniqueness and homogeneity of the three major monomer hemoglobins, called components II, III, and IV (or alternatively GMH2, 3, and 4) that have been reproducibly isolated and characterized in this laboratory 3–8, 11–14, 24–39. Recently, the solution structure of the CO‐ligated Fe 2+ (reduced, ferrous) form of recombinant GMH4 (GMH4CO) was determined,38, 39 making it the first structure to be determined of one of our highly characterized monomer hemoglobins.…”
Section: Introductionmentioning
confidence: 70%
“…Whereas the functional implications of this substitution were immediately clear, the true extent of the globin heterogeneity present in these cells was unrecognized 15–23. Vinogradov and co‐workers1 were the first to separate the G. dibranchiata erythrocyte contents into monomeric and polymeric hemoglobins, but further realization of extensive heterogeneity in the monomeric globin fraction was not recognized until the work of Parkhurst et al2 and our group 3–8, 11–14…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The studies demonstrated that K A/B is determined by steric interactions of the peripheral side chains attached to pyrrole rings I and II of the heme, i.e., the side chains at positions 2, 3, 7, and 8 (Figure 1), with the surrounding amino acid residues in the heme pocket. 11,14,18,29,30,36,41 In fact, K A/B has been shown to be greatly affected by replacement of the amino acid residues in close proximity to these heme side chains. 14,18,41 The heme orientational disorder demonstrated that the molecular recognition upon insertion of the heme into the Mb heme pocket is not as strict as that for the formation of usual enzyme−substrate complexes.…”
mentioning
confidence: 99%